2023
DOI: 10.3390/metabo13030442
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Phytocannabinoids and Structural Insights: A Review

Abstract: Cannabis belongs to the family Cannabaceae, and phytocannabinoids are produced by the Cannabis sativa L. plant. A long-standing debate regarding the plant is whether it contains one or more species. Phytocannabinoids are bioactive natural products found in flowers, seeds, and fruits. They can be beneficial for treating human diseases (such as multiple sclerosis, neurodegenerative diseases, epilepsy, and pain), the cellular metabolic process, and regulating biological function systems. In addition, several phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 112 publications
(157 reference statements)
0
9
0
1
Order By: Relevance
“…These compounds are believed to have therapeutic potential for treating conditions such as mood disorders, neurological disorders, cancer, diabetes, and pain [ 3 , 4 ]. The current knowledge of the phytocannabinoids’ biosynthetic pathways remains limited [ 5 , 6 ]. In addition, the introduction of novel traits is difficult to accomplish without changing the cannabinoid profile.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are believed to have therapeutic potential for treating conditions such as mood disorders, neurological disorders, cancer, diabetes, and pain [ 3 , 4 ]. The current knowledge of the phytocannabinoids’ biosynthetic pathways remains limited [ 5 , 6 ]. In addition, the introduction of novel traits is difficult to accomplish without changing the cannabinoid profile.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have a long history with Cannabis sativa, with evidence of cultivation dating back as far as 10,000 years (12,82). The World Health Organization (WHO) reported that Cannabis is the most widely cultivated, trafficked and abused illicit drug, and it constitutes over half of worldwide drug seizures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Medical research on Cannabis has primarily focused on isolated THC (Δ9-Tetrahydrocannabinol), and CBD (Cannabidiol) but there are hundreds of other chemical constituents in Cannabis, including Cannabinoids and terpenes .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, hemp consumption has been spurred on by its wide range of properties and uses from Indian Himalayan civilization to another civilization through consecutive millennia (3)(4)(5)(6)(7)(8)(9)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93). Cannabis research work remains years behind than other crops because of the long legacy of prohibition and stigmatization (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Hemp has historically been attractive for its top-quality fibre and edible oil (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytocannabinoids are characteristic metabolites of Cannabis sativa L. Approximately 200 cannabinoids have been discovered from this species, each with unique therapeutic and/or abuse potential. These bioactive terpenoids have recently been discovered in Rhododendron and Radula species, as well as in certain legumes and fungi ( Gülck and Møller, 2020 ; Govindarajan et al, 2023 ; Hesami et al, 2023 ; Sainz Martinez et al, 2023 ). Cannabinoids are insoluble in water but soluble in alcohols, non-polar organic solvents (e.g., ether and hexane), and lipids.…”
Section: Introductionmentioning
confidence: 99%